Pengembangan LKPD Terintegrasi Etnosains Batik Semarang untuk Meningkatkan Literasi Kimia Siswa - Fitri Siami; Woro Sumarni; Sudarmin Sudarmin; Harjono Harjono (Jurnal Penelitian Pendidikan IPA, 2023)
The problem of this research is developments in the 21st century that require someone to have special abilities, namely chemical literacy. This is in accordance with the 2013 curriculum which demands responsiveness to developments in science, culture, technology, and the arts. The aim of this research is to develop worksheets and improve students' chemical literacy skills in acid-base material. The method used uses a research and development approach with a research flow that adopts the 4-D development model, i.e. definition, design, development, and dissemination. However, this research was carried out up to the 3-D stage, i.e. definition, design, and development. The feasibility of the LKPD is seen through the assessment of material expert validators at 92.86% and media validators at 96.67% in the "Very Feasible" category. The effectiveness of the LKPD can be seen from the pretest-posttest results with an N-Gain of 0.81 in the high category. The results of chemical literacy analysis on the content, epistemic, and procedural knowledge aspects were 94.30%, 81.39%, and 64.45%. Meanwhile, context and competency aspects produced 84.07% and 92.22%. The developed LKPD was declared feasible by experts in the very feasible category and declared effective because it obtained a high N-Gain value.